Human Bile Contains Cholangiocyte Organoid-Initiating Cells Which Expand as Functional Cholangiocytes in Non-canonical Wnt Stimulating Conditions - Roos, Floris J. M.; Verstegen, Monique M. A.; Muñoz Albarinos, Laura; Roest, Henk P.; Poley, Jan-Werner; Tetteroo, Geert W. M.; IJzermans, Jan N. M.; van der Laan, Luc J. W. (Frontiers in Cell and Developmental Biology, 2021)
Diseases of the bile duct (cholangiopathies) remain a common indication for liver transplantation, while little progress has been made over the last decade in understanding the underlying pathophysiology. This is largely due to lack of proper in vitro model systems to study cholangiopathies. Recently, a culture method has been developed that allows for expansion of human bile duct epithelial cells grown as extrahepatic cholangiocyte organoids (ncECOs) in non-canonical Wnt stimulating conditions. These ncECOs closely resemble cholangiocytes in culture and have shown to efficiently repopulate collagen-scaffolds that could act as functional biliary tissue in mice. Thus far initiation of ncECOs required tissue samples, thereby limiting broad patient-specific applications. Here we report that bile fluid, which can be less invasively obtained and with low risk for the patients, is an alternative source for culturing ncECOs. Further characterization showed that bile-derived cholangiocyte organoids (ncBCOs) are highly similar to ncECOs obtained from bile duct tissue biopsies. Compared to the previously reported bile-cholangiocyte organoids cultured in canonical Wnt-stimulation conditions, ncBCOs have superior function of cholangiocyte ion-channels and are able to respond to secretin and somatostatin. In conclusion, bile is a new, less invasive, source for patient-derived cholangiocyte organoids and makes their regenerative medicine applications more safe and feasible.